APLIKASI PENILAIAN KINERJA KARYAWAN DENGAN METODE GRAPHIC RATING SCALE BERBASIS WEB PADA PT. TRI KARYA CEMERLANG MEDAN - Halawa, Fangalulu; Purba, Swingly; Siburian, Ruth Meivera (LPPM ISTP, 2024)
Performance appraisal is one way to develop human resources. PT. Tri Karya Cemerlang Medan is a company that always maintains the quality of human resources. One way to do this is to carry out employee performance assessments once a month, but the process is still carried out manually and is only carried out by one person, as is the calculation process. This results in subjective assessment results. Therefore PT. Tri Karya Cemerlang Medan requires a computerized employee performance assessment application and comprehensive assessment accommodation from both employees and management. With the Graphic Rating Scale method, the calculation process is able to accommodate employee performance assessments which consist of several indicators. The application was built on a web basis so that it provides users with the opportunity to access freely and anywhere.